A case of T-cell acute lymphoblastic leukemia in retroviral gene therapy for ADA-SCID - Daniela Cesana; Maria Pia Cicalese; Andrea Calabria; Pietro Merli; Roberta Caruso; Monica Volpin; Laura Rudilosso; Maddalena Migliavacca; Federica Barzaghi; Claudia Fossati; Francesco Gazzo; Simone Pizzi; et al. (Nature Communications, 2024)
Abstract Hematopoietic stem cell gene therapy (GT) using a γ-retroviral vector (γ-RV) is an effective treatment for Severe Combined Immunodeficiency due to Adenosine Deaminase deficiency. Here, we describe a case of GT-related T-cell acute lymphoblastic leukemia (T-ALL) that developed 4.7 years after treatment. The patient underwent chemotherapy and haploidentical transplantation and is currently in remission. Blast cells contain a single vector insertion activating the LIM-only protein 2 (LMO2) proto-oncogene, confirmed by physical interaction, and low Adenosine Deaminase (ADA) activity resulting from methylation of viral promoter. The insertion is detected years before T-ALL in multiple lineages, suggesting that further hits occurred in a thymic progenitor. Blast cells contain known and novel somatic mutations as well as germline mutations which may have contributed to transformation. Before T-ALL onset, the insertion profile is similar to those of other ADA-deficient patients. The limited incidence of vector-related adverse events in ADA-deficiency compared to other γ-RV GT trials could be explained by differences in transgenes, background disease and patient’s specific factors.